Similarities and Differences: Inheritance Distribution in Balinese Customary Law Perspective of Islamic Law - Syafaat, Mely Khoironi (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2025)
In the context of plurality of laws in Indonesia, Islamic inheritance law and Balinese customary inheritance law show fundamental differences but also interesting meeting points to study. Balinese customary laws rooted in traditional values and patrilineal kinship systems tend to place men as the primary heirs. Meanwhile, Islamic inheritance law which is sourced from the Qur’an and Hadith emphasizes the principles of justice, balance, and legal certainty that give rights to all legal heirs, including women. In a society that continues to undergo social change, the interaction between these two legal systems creates complex dynamics, especially in terms of the implementation of inheritance distribution. This article aims to identify and analyze the similarities and differences between Balinese customary inheritance law and Islamic inheritance law, both in terms of basic principles, inheritance structure, and practice in the field. The research method used is a qualitative approach with a literature study, which includes analysis of primary and secondary legal sources. The results of the study show that although there are significant differences in terms of the hereditary system and the position of women as heirs, they have similarities in upholding family values and social responsibility. I hope that the results of this writing can contribute to the development of national inheritance laws that are responsive to cultural diversity and religious norms in Indonesia, as well as encourage the creation of a harmonious, fair, and contextual legal system for multicultural societies.